SYNTHESIS OF TETRAKIS-N,N,N-TRIMETHYLAMMONIUMMETHYL-C-3,4-DIMETHOXYPHENYLCALIX[4]RESORCINARENE IODIDE BASED VANILLIN AND ITS ANTIDOTE ACTIVITY FOR CHROMIUM(VI) INTOXICATION - Suryadi Budi Utomo; Jumina Jumina; Dwi Siswanta; Mustofa Mustofa (Universitas Gadjah Mada, 2013)
A research has been conducted to synthesize tetrakis-N,N,N-trimethylammoniummethyl-C-3,4-dimethoxyphenylcalix[4]resorcinarene iodide from vanillin and investigate its antidote capability for Cr(VI) intoxication. The synthesis was carried out in four steps i.e. (1) O-alkylation of 4-hydroxy-3-methoxybenzaldehyde, (2) HCl-catalyzed condensation of 3,4-dimethoxybenzaldehyde with resorcinol, (3) Mannich reaction of C-3,4-dimethoxyphenylcalix[4]resorcinarene with formaldehyde and dimethylamine in the presence of HCl to yield tetrakis-N,N-dimethylaminomethyl-C-3,4-dimethoxyphenylcalix[4]resorcinarene, and (4) treatment the Mannich base with methyl iodide to produce the quaternary ammonium salt of tetrakis-N,N,N-trimethylammoniummethyl-C-3,4-dimethoxyphenylcalix[4]resorcinarene iodide. According to the analysis of 1H-NMR spectrometer, the targeted compounds tend to exist in the chair (C2h) conformation. The capability of resorcinarene for Cr(VI) antidote was examined by orally injection method on mice groups. Based on LD50 determination, the resorcinarene was classified as non toxic compound according to Loomis criteria. Therapeutic using quaternary ammonium-modified resorcinarene was able to reduce metal concentrations of Cr(VI) in liver, kidney, and serum in the magnitude of 78.30; 85.72, and 88.79%, respectively. The higher dose of drug administered the greater decrease in the level of heavy metal. Judging from the amount of milligrams of reduced chromium per gram of organ, kidney is the organ having highest decreasing metal concentrations.